Susceptibility and compatibility of biomphalaria tenagophila from the Río de la Plata basin with schistosoma mansoni from Brazil - Borda, Carlos Edgardo; Rea, María Josefa Felisa (Ministério da Saúde. Instituto Oswaldo Cruz, 2010)
Schistosomiasis has expanded to southern parts of Brazil. Between 2005-2007 the dispersion and the proliferation of Biomphalaria tenagophila was verified in the province of Corrientes near the Brazilian border. In order to study the possibility that schistosomiasis might spread into the basins of the Paraná and Uruguay Rivers, 440 B. tenagophila collected from 10 populations groups were experimentally exposed to infection with Schistosoma mansori of the SJ2 strain. Snails from five localities were susceptible. Frandsen’s index (TCP/100) shows that those snails from Mirungá (11%), Aguacerito (2%) and Curupicay (2%) were Class I and not very compatible. Meanwhile, snails from Copra (6%) and Pay-Ubre (22%), in the Paraná River basin, were Class II and poorly compatible.
Keywords: Compatibility; Biomphalaria tenagophila; Río de la Plata basin; Schistosoma mansoni